The road to facility management. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to gain insight into facility management in Portugal as well as in Europe and what a facility management study programme must entail in Portugal in order to implement this.Design/methodology/approach – The paper describes the mixed‐methods approach. Both qualitative and quantitative methods are used based on extensive literature research of the subject. Semi‐structured interviews were held with ten professionals from the FM field. The quantitative method was in the shape of a questionnaire sent to 40 professionals in Europe.Findings – The results show that Portugal is not on the same level as the rest of Europe when it comes to FM. Also, FM is rather of a technical nature and lacks service orientation and managerial elements. Moreover, Portugal should first focus on creating awareness about the field of FM and provide FM study programmes accordingly. Research shows that this could be a lengthy process.Originality/value – Currently there is no facility management study programme offered in Portugal. However, by gaining insight into this field and how facility management is of great added value to the market, a step closer to implementing a study programme is taken.